Love, Lucas - Sedgwick, Chantele (New York : Scholastic, Inc., 2015)
"Grieving for her brother Lucas, Oakley agrees to spend a few months with her mother at a beach house, where a notebook of letters from Lucas challenges her to again enjoy life, but a budding romance reminds her of the chances Lucas will never have." (Source: WorldCat)
Keywords: Grief -- Fiction; Brothers and sisters -- Fiction; Letters -- Fiction